Effect of lipoarabinomannan from Mycobacterium avium subsp avium in Freund’s incomplete adjuvant on the immune response of cattle - Colavecchia,S.B. (2012)
The aim of the present study was to determine whether lipoarabinomannan (LAM), in combination with Freund’s incomplete adjuvant (FIA), was able to improve cell-mediated and antibody-mediated immune responses against ovalbumin (OVA) in cattle. Twenty-three calves were assigned to four treatment groups, which were subcutaneously immunized with either OVA plus FIA, OVA plus FIA and LAM from Mycobacterium avium subsp avium, FIA plus LAM, or FIA alone. Lymphoproliferation, IFN-γ production and cell subpopulations on peripheral blood mononuclear cells before and 15 days after treatment were evaluated. Delayed hypersensitivity was evaluated on day 57. Specific humoral immune response was measured by ELISA. Inoculation with LAM induced higher levels of lymphoproliferation and IFN-γ production in response to ConA and OVA (P < 0.05). Specific antibody titers were similar in both OVA-immunized groups. Interestingly, our results showed that the use of LAM in vaccine preparations improved specific cell immune response evaluated by lymphoproliferation and IFN-γ production by at least 50 and 25%, respectively, in cattle without interfering with tuberculosis and paratuberculosis diagnosis.